An experimental cost model for composite parts using vacuum assisted resin transfer moulding (VARTM) - Vogt, Christian (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MScEng (Mechanical and Mechatronic Engineering))--University of Stellenbosch, 2011.